ANALISIS IMPLEMENTASI STÁNDAR TENAGA KEPENDIDIKAN DI SMP NEGERI 4 KUTA UTARA - Gede Riyan Sedana Putra; Ni Luh Novita Deviana; Ni Luh Bella Amanda Sari; I Wayan Lasmawan; Ni Wayan Rati (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This research is motivated by the large number of educational units that have teaching staff with conditions that do not meet the ideal qualifications according to national regulations. The problem is focused on analyzing the level of conformity between the real profile of educators and educational staff at SMP Negeri 4 Kuta Utara with the Regulation of the Minister of Primary and Secondary Education Number 21 of 2025. This study is included in the type of qualitative research with the data collection method through the study of school portfolio documentation and strengthened through in-depth interviews with key informants. The collected data is then analyzed using qualitative descriptive techniques through the stages of data reduction, narrative presentation of information, and ending with the drawing of valid conclusions. The research results show that the profile of the teaching staff at the school has fully met the regulatory criteria with the achievement of the percentage of academic qualifications of bachelor's degree reaching 100 percent, ownership of teaching certificates of 97.2 percent, and a teaching linearity level of 97.2 percent. However, the aspect of educational staff has not been met comprehensively because this institution only has four of the six types of required staff classifications due to the lack of laboratory assistants and librarians. The main conclusion emphasizes the need for periodic recruitment proposals to local governments to optimize the operation of school facilities and infrastructure to support the quality of education services on an ongoing basis. ABSTRAK Penelitian ini dilatarbelakangi oleh banyaknya satuan pendidikan yang memiliki staf pendidik dengan kondisi belum memenuhi kualifikasi ideal sesuai regulasi nasional. Masalah difokuskan pada analisis tingkat kesesuaian antara profil riil pendidik serta tenaga kependidikan di SMP Negeri 4 Kuta Utara dengan Peraturan Menteri Pendidikan Dasar dan Menengah Nomor 21 Tahun 2025. Studi ini termasuk ke dalam jenis penelitian kualitatif dengan metode pengumpulan data melalui studi dokumentasi portofolio sekolah serta diperkuat lewat wawancara mendalam bersama informan kunci. Data yang telah terkumpul selanjutnya dianalisis menggunakan teknik deskriptif kualitatif melalui tahapan reduksi data, penyajian informasi secara naratif, dan diakhiri dengan penarikan kesimpulan yang valid. Hasil riset menunjukkan bahwa profil tenaga pendidik di sekolah tersebut sepenuhnya telah memenuhi kriteria regulasi dengan capaian persentase kualifikasi akademik sarjana mencapai 100 persen, kepemilikan sertifikat pendidik sebesar 97,2 persen, serta tingkat linearitas mengajar sebesar 97,2 persen. Namun demikian, aspek tenaga kependidikan belum terpenuhi secara komprehensif karena institusi ini baru memiliki empat dari enam jenis klasifikasi ketenagaan yang diwajibkan akibat ketiadaan laboran dan pustakawan. Simpulan utama menegaskan perlunya usulan rekrutmen formasi secara berkala kepada pemerintah daerah guna mengoptimalkan operasional sarana prasarana sekolah demi menunjang kualitas mutu layanan pendidikan secara berkelanjutan.